Estimates of Coefficient for Certain Subclasses of k-Fold Symmetric Bi-Univalent Functions - Juma, Abdul Rahman S.; Al-Fayadh, Ali; Shehab, Nihad H. (Iraqi Journal of Science, 2022)
In the present paper, the authors introduce and investigates two new subclasses and, of the class k-fold bi-univalent functions in the open unit disk. The initial coefficients for all of the functions that belong to them were determined, as well as the coefficients for functions that belong to a field determining these coefficients requires a complicated process. The bounds for the initial coefficients and are contained among the remaining results in our analysis are obtained. In addition, some specific special improver results for the related classes are provided.